Effectiveness of Online Teaching from Teachers’ Perspectives - Nguyen, Thanh Lam; Nguyen, Thi Le; Ho, Thi Quynh Nhu; Tran, Thi Quynh Nhu; Do, Thu Thuy; Hoang, Tuan Nguyen; Nguyen, Thi Hai Van; Truong, Thi Thu Ha (Journal of Technical Education Science, 2022)
The COVID-19 pandemic has been posing substantial challenges to every aspect of human society over the last two years. In Vietnam, all educational institutions have struggled to quickly build and operate their online systems while their teachers have tried their best to adapt to the online environment. Fortunately, the EMVITET Erasmus+ capacity-building project has been punctually and effectively implemented since early 2019 to provide its six partners in Vietnam with significant support to enhance their digital competencies. Several capacity-building activities in the project have been conducted so far. This paper aims at assessing the impacts of the project by evaluating the effectiveness of online teaching at the partner institutions from the teachers’ perspectives after about 3 years of project implementation. Based on the responses from 101 teachers collected with a self-completed online questionnaire, it is found that the EMVITET project has greatly supported the partner institutions in successfully deploying an online environment for their teaching-learning activities. Especially, online teaching has proved its effectiveness in improving the diversity of educational activities, collaboration among colleagues, knowledge transmission, faster interaction among lecturers and students as well as the diverse approaches for teachers to evaluate student learning, students’ diligence, students’ engagement in their studies and research, and soft skills during their study online, among others.